2002
DOI: 10.2298/vsp0206593m
|View full text |Cite
|
Sign up to set email alerts
|

Age and body mass related changes of cardiovascular risk factors in women with polycystic ovary syndrome

Abstract: Polycystic ovary syndrome (PCOS) is considered a metabolic disorder closely related to obesity, insulin resistance (IR), hyperinsulinemia and unfavorable lipid profile, all increasing the risk for the occurrence of cardiovascular diseases. The aim of this study was to assess age and body mass index (BMI) related changes of cardiovascular risk factors in 90 women with PCOS. The cut-off age point was 30 years and for BMI 27.8 kg/m2. In all patients systolic and diastolic blood pressure (BP), metabolic parameters… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
4
0
2

Year Published

2004
2004
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 22 publications
3
4
0
2
Order By: Relevance
“…However, it also might suggest that the worsening of IR with aging is more pronounced in women with PCOS than in healthy women. An earlier crosssectional study also reported a worsening of IR in women with PCOS >30 years of age (21). On the other hand, in a prospective study in women with PCOS who showed no increase in BMI, waist circumference, or waist-to-hip ratio during a 10-year follow-up, plasma insulin levels and area under the OGTT curve also remained unchanged (17).…”
Section: Discussionmentioning
confidence: 85%
“…However, it also might suggest that the worsening of IR with aging is more pronounced in women with PCOS than in healthy women. An earlier crosssectional study also reported a worsening of IR in women with PCOS >30 years of age (21). On the other hand, in a prospective study in women with PCOS who showed no increase in BMI, waist circumference, or waist-to-hip ratio during a 10-year follow-up, plasma insulin levels and area under the OGTT curve also remained unchanged (17).…”
Section: Discussionmentioning
confidence: 85%
“…A number of reports have shown however, that at baseline insulin levels are higher in PCOS women, mainly after 25 to 30 years of age (18,60). On the other hand, other studies have denied that insulin increases in PCOS over time (4,6,13,19,21,23,62,64,65), particularly in those patients in whom BMI, WC, and WHR remained stable. The baseline concentration of fasting insulin was in fact reported to decrease (17) or remain stable (4,15) during the aging process.…”
Section: Discussionmentioning
confidence: 99%
“…The baseline concentration of fasting insulin was in fact reported to decrease (17) or remain stable (4,15) during the aging process. It is possible that a decrease in androgens (65) and an increase in fat distribution abnormalities influences insulin levels over time; additionally, different populations, or different study eligibility might explain possible inconsistencies across studies.…”
Section: Discussionmentioning
confidence: 99%
“…Par rapport à la parité, la proportion des patientes nullipares court un risque de 1,61 fois de contracter ce syndrome. Cette observation corrobore avec les études épidémiologiques qui constatent que les femmes nullipares avec SOMPK sont prédominantes [ 17 , 18 ].…”
Section: Discussionunclassified